Electron energy spectrum and oscillator strengths of quantum transitions in double quantum ring nanostructure driven by electric field - Makhanets, O.M.; Gutsul, V.I.; Kuchak, A.I. (Condensed Matter Physics, 2018)
The effect of homogeneous electric field on the energy spectrum, wave functions of electron and oscillator
strengths of intra-band quantum transitions in a double cylindrical quantum ring (GaAs/AlxGa1−xAs) is studied
within the approximations of effective mass and rectangular potentials. The calculations are performed using
the method of expansion of quasiparticle wave function over a complete set of cylindrical wave functions obtained as exact solutions of Schrödinger equation for an electron in a nanostructure without electric field. It is
shown that the electric field essentially affects the electron localization in the rings of a nanostructure. Herein,
the electron energies and oscillator strengths of intra-band quantum transitions non-monotonously depend on
the intensity of electric field. У моделi ефективних мас та прямокутних потенцiалiв дослiджено вплив однорiдного електричного поля
на енергетичний спектр, хвильовi функцiї електрона та сили осциляторiв внутрiшньозонних квантових
переходiв у подвiйних напiвпровiдникових (GaAs/AlxGa1−xAs) цилiндричних квантових кiльцях. Розрахунки виконанi методом розкладу хвильових функцiй квазiчастинки за повним набором цилiндричних
хвильових функцiй, отриманих як точний розв’язок рiвняння Шредiнгера для електрона в наноструктурi
за вiдсутностi електричного поля. Показано, що електричне поле суттєво впливає на локалiзацiю електрона у системi нанокiлець. При цьому як енергiї електрона, так i сили осциляторiв внутрiшньозонних
квантових переходiв немонотонно залежать вiд величини напруженостi електричного поля.